2013
DOI: 10.1093/brain/awt005
|View full text |Cite
|
Sign up to set email alerts
|

Visual exploration in Parkinson’s disease and Parkinson’s disease dementia

Abstract: Parkinson's disease, typically thought of as a movement disorder, is increasingly recognized as causing cognitive impairment and dementia. Eye movement abnormalities are also described, including impairment of rapid eye movements (saccades) and the fixations interspersed between them. Such movements are under the influence of cortical and subcortical networks commonly targeted by the neurodegeneration seen in Parkinson's disease and, as such, may provide a marker for cognitive decline. This study examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 65 publications
3
55
0
2
Order By: Relevance
“…According to the current model of neurophysiology, accurate rapid eye movement control is generated by integrating cortical input from the frontal, supplemental, and parietal eye fields through circuits of thalamus, basal ganglia, and the superior colliculus (9). Some of these neuronal pathways are involved in the neurodegeneration of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current model of neurophysiology, accurate rapid eye movement control is generated by integrating cortical input from the frontal, supplemental, and parietal eye fields through circuits of thalamus, basal ganglia, and the superior colliculus (9). Some of these neuronal pathways are involved in the neurodegeneration of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that, independent of the trigger mechanism (internal or external), saccades are dysfunctional in Parkinson’s disease, due to hypometria (mostly) or hypermetria, delayed initiation, or even inadvertent elicitation. In conjunction with prolongation of fixation, a disease-specific impact on the networks directing visual exploration has been postulated (Archibald et al , 2013). …”
Section: Pathophysiologymentioning
confidence: 99%
“…Meppelink et al (2009) found that visual hallucinations were associated with reduced object processing in higher order visual cortex and reduced bottom-up input to the prefrontal cortex. In addition, Parkinson disease patients also have some deficits in eye movement and attentional control, though these could be due to oculomotor loop or other dysfunction (Chambers and Prescott, 2010; Archibald et al, 2013). …”
Section: Empirical Research Examining the Functions Of The Caudate Tailmentioning
confidence: 99%